La belleza: anotaciones para apuntar a una visión más unitaria de Gabriel Dondo - Gallardo Pirovano, Juan Luis (2013)
God is the Supreme Beauty. What exists in the world and what the human being creates with his wit is “beauty”, a beauty that participates in beauty. The Christian artist must discover and aknowledge the joy and beauty of his faith in the various areas of everyday life. Art is a manifestation of the human being, of his ideals, joys, concerns, purpose, values and experiences that lead his life.